Pacific artistic communities in Australia: Gaining visibility in the art world. (3rd August 2022) - Le Roux, Géraldine
Abstract: This article shows that although Pacific arts began to be largely recognised in Australia in the 1990s, Pacific artists based in Australia remained mostly invisible in the contemporary art scene until the mid‐2000s. I aim to demonstrate how Pacific artists and curators—who in some cases collaborated with Aboriginal and Torres Strait Islander artists and curators—have made visible myriad Pacific identities and social trajectories in Australian cities. Exhibitions reveal and highlight multiple experiences of Pacific people residing in Australia, for whom Pacific cultures are partly mediated by the experiences of their relatives, popularised by museum collections and coloured by the gaze of non‐Pacific people. This article is built around two cultural events that have not previously received scholarly attention, a group show curated in Sydney by Māori artist and cultural worker Keren Ruki and a triennial in Brisbane imagined and organised by Bundjalung Yugambeh (Aboriginal Australian) artist and curator Jenny Fraser. It addresses how narratives in the 2000s were often connected to objectives of empowerment and the necessity to build a future for Pacific peoples in Australian society.